Experiences With Parents and Youth Physical Health Symptoms and Cortisol: A Daily Diary Investigation. (12th December 2014) - Lippold, Melissa A.; McHale, Susan M.; Davis, Kelly D.; Almeida, David M.; King, Rosalind B.
Abstract : Using daily diary data, this study examined the associations between positive and negative parent–youth experiences and youth cortisol and physical health symptoms among a sample of adolescents ( N = 132, mean age = 13.39). On days when girls reported more negative experiences than usual, they exhibited more physical health symptoms and flatter evening cortisol slopes than usual. Negative experiences with mothers were associated with higher dinner and bedtime youth cortisol levels (between‐person). Daily positive experiences with fathers were linked with lower dinner cortisol levels. Youth with high levels of negative experiences, on average, were less sensitive to daily variation in negative experiences than youth who experienced lower parental negativity. We discuss the benefits of a daily diary approach.